Research and Application of Non-traditional Chemical Stabilizers on Bauxite 3 Residue (Red Sand) Dust Control - Ding, Xuhan (Curtin University, 2018)
Although the treatment of red sand dust pollution is challenging, one potential approach to mitigate such issue is the application of non-traditional chemical stabilizers. In this paper, the Mechanisms of dust emission and chemical stabilization of red sand are proposed, the performance of different non-traditional stabilizer on dust control is studied and compared, and dust control performance and the change of mechanical properties are correlated for a sound red sand dust control strategy.